PERLINDUNGAN HUKUM TERHADAP HAK PEKERJA ANAK BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK - Adi Putro; Mexsasai Indra; Abdul Ghafur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
In order to guarantee the protection of working children has been issued legislation, which is no principle prohibits children to work and when compelled to work, then normatively children must be guaranteed adequate legal protection. Therefore, the central government and local governments should strive oversee the implementation of legal products in order to protect the interests and constitutional rights of the child.This type of research is a normative legal research writer. Normative legal research is legal research doctrinaire, also referred to as a research library or study documents that put emphasis on secondary data. Data collection techniques in this research is the study of literature, the author quotes from books, literature, or supporting books relating to the issues to be studied. The results of this thesis research legal protection for children can be interpreted any attempt berbgai legal protection of the freedoms and rights of children as well as the various interests related to child welfare. The problem of child labor is influenced by factors causing child labor, namely: economic factors, factors of parents, environmental factors. The suggestion author on the legal protection of the rights of child workers under Act No. 35 of 2014 on the protection of children, namely: First, the Government of Indonesia to revise Law No. 35 of 2014 on Child Protection that regulates the provisions or minimum ages for work permits, establish appropriate regulations regarding work hours for child labor and conditions of work for child workers, determine the types of work that is harmful to the child laborers.second, For the parents are expected to be more directed his son to study well in school up to high school level to potentially improve the family economy. Third, the Community should contribute to oversee all the activities of children so that children do not fall in an environment of likelihood of child endangerment.Keywords: Protection-Rights of the Child-Child Protection.